2017
DOI: 10.1080/17474086.2017.1346471
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and neonatal alloimmune thrombocytopenia: evidence based antenatal and postnatal management strategies

Abstract: Fetal and neonatal alloimmune thrombocytopenia (FNAIT) is a relatively rare but potentially lethal disease, leading to severe bleeding complications in 1 in 11.000 newborns. It is the leading cause of thrombocytopenia in healthy term-born neonates. Areas covered: This review summarizes the antenatal as well as postnatal treatment, thus creating a complete overview of all possible management strategies for FNAIT. Expert commentary: The optimal antenatal therapy in order to prevent bleeding complications in preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 69 publications
2
35
0
5
Order By: Relevance
“…Further investigation will be necessary to explain the presence of granulocyte-specific antibodies in never allo-exposed women and primiparous women. Expression of the human platelet antigen 1a (HPA-1a) on glycoprotein αvβ3 on placental endothelial cells is one of the reasons for alloimmunization against HPA-1a already in the first pregnancy [19]. However, most of the involved granulocyte antigens are not expressed on placental tissue, and therefore, only exposure of these antigens on fetal granulocytes seems to be the immunizing trigger during pregnancy.…”
Section: Pathologymentioning
confidence: 99%
“…Further investigation will be necessary to explain the presence of granulocyte-specific antibodies in never allo-exposed women and primiparous women. Expression of the human platelet antigen 1a (HPA-1a) on glycoprotein αvβ3 on placental endothelial cells is one of the reasons for alloimmunization against HPA-1a already in the first pregnancy [19]. However, most of the involved granulocyte antigens are not expressed on placental tissue, and therefore, only exposure of these antigens on fetal granulocytes seems to be the immunizing trigger during pregnancy.…”
Section: Pathologymentioning
confidence: 99%
“…Comparison with other studies is relatively difficult due to the fact that the majority of authors have calculated FBS-related fetal loss and adverse outcome rates in relation to the total number of treated fetuses, rather than the total number of procedures performed in this population, which, by definition, would result in an higher reported rate of such complications [9, 12, 16, 18-21] (Appendix 1). Two reports did calculate the risk compared to the total number of procedures: Berkowitz et al [21] reported a rate of pregnancy loss similar to our data (0.6 vs. 0.8%) with, however, a rate of other adverse outcomes five times higher than in our series (6 vs. 0.8%), and Overton et al [19] reported a fetal loss rate of 2.4% (2/84 procedures) in a small series of 12 cases, including an unexplained fetal death occurring 7 days after an uncomplicated PLT IUT.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, labor occurred 5 days after the procedure, while in 2 cases, induction of labor was planned because of severe maternal pre-eclampsia with HELLP syndrome at 29 and 32 +2 weeks, and in one case spontaneous labor occurred at 33 +5 weeks, 2 weeks after the second FBS, in a woman with a history of premature labor at 35 weeks’ gestation (Table 2). Bussel and Primiani [12] reported a similar rate of premature birth (2.1%) in the subgroup undergoing FBS, while in the majority of the other studies, the prematurity rate was reported as being between 7.8 and 75%, reflecting a higher rate of FBS-related adverse pregnancy outcome or, in one series, delivery was undertaken at 32 weeks routinely [19]. We suggest that a detailed discussion of the potential risks associated with FBS (in very experienced hands only), and the role it may play in allowing a safe vaginal delivery, should be discussed with these patients, many of whom have had previous vaginal deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many of the FNAIT instance, the illness presents as, petechiae, hematomas, haemoptysis, retinal bleeding and haematuria [57,67]. Occasionally, the bleeding due to FNAIT is diagnosed during foetal life in ultrasound abnormalities [68]. Without routine screening for HPA antibodies the disease is mostly detected after the delivery of the first affected child.…”
Section: Foetal/neonatal Alloimmune Thrombocytopenia (Fnait)mentioning
confidence: 99%